A reconfigurable printed dipole antenna using RF PIN diodes. Issue 5 (May 2014) - Abbasiniazare, Seyyedpayam; Manoochehri, Omid; Forooraghi, Keyvan
Abstract A frequency switchable printed dipole antenna is proposed for multiband application. The electrical length of the dipole can be changed by controlling the pin diodes states so that the antenna can operate in three different frequency bands. The larger/smaller of the current path, the smaller/larger of the resonance frequency can be obtained. Three resonant frequencies from 200 to 1400 MHz are selected in this bandwidth and proper matching is achieved for all resonant frequencies. Also, a pair of capacitive stubs at the end of dipole have been used for achieving a resonant frequency lower than a standard dipole of comparable length. For optimizing the antenna structure, a parametric analysis has been performed by calculating the length and width of radiators with formulas. All simulated results have been confirmed with measured data. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1151–1155, 2014